Irritation Test and Effectiveness of The Clean Power Activated Charcoal Palm Shells (Elaeis guineensis Jacg) as Adsorbent Dirt on The Hair - Uce Lastari; Syamsurizal Syamsurizal; Faizar Farid (Indonesian Journal of Pharmaceutical Research, 2021)
The dirty and itchy scalp is very annoying in appearance, which is the onset of dandruff. Dandruff is due to the accumulation of dead skin cells, dry and oily scalp as well as the presence of skin infections and fungi in the head. To avoid the onset of dirt or dandruff to hair, it is necessary to do cleaning regularly using cosmetics one of them is active charcoal-based shampoo palm kernel shells. The capability of palm kernel shells can absorb dirt twice from commercial active charcoal to cleanse the skin to the fullest. This research aims to effectively absorption of the dirt in Invitro on the active charcoal shampoo of palm shells with a concentration of 12%. Invitro tests the effectiveness of the impurities absorbent by using a turbidimetry tool with a Nephelometric Turbidity Unit value or frequency number. While the irritation test is done on 10 people panelists. Comparative control used commercial shampoo as a positive control and base shampoo as a negative control. The results showed that a 12% palm shell activated charcoal shampoo provided an NTU value of 11,400 while a commercial shampoo gave an NTU value of 786. No panelists have irritation on the scalp. From the obtained results can be concluded that the active oil palm Shell Shampoo has the absorbent power to the dirt from a commercial shampoo and safe to use.